Good Practices for Consumer Protection and Financial Literacy in Europe and Central Asia : A Diagnostic Tool - Rutledge, Susan L.; Annamalai, Nagavalli; Lester, Rodney; Symonds, Richard L. (World Bank, Washington, DC, 2013)
This paper discusses how the importance of adequate consumer protection and financial literacy for the long-term stability of the financial sector, has been highlighted by the recent turmoil in financial markets worldwide. It presents a set of Good Practices for Consumer Protection and Financial Literacy, developed by the World Bank's Europe and Central Asia Region, using international experience as a guide. The Good Practices provide a practical tool for systematic analysis of laws, regulations and institutions involved in consumer protection and financial literacy, and allow detailed cross-country comparisons. The paper provides the four key concepts on which they are based: consumer disclosure should be simple, easy to understand and comparable; abusive business practices by financial service providers should be prohibited; consumers should have an easy, inexpensive and speedy method of resolving disputes with financial institutions; and financial education should be available to consumers so that they can understand financial services and products and make informed decisions.